Analysis Corporate Zakat Collection in National Zakat Institutions: Perspectives Normative and Strategic Approaches - Edwin Nurul Syafarudin (JURNAL HAKAM, 2026)
This article examines the implementation of corporate zakat within national zakat institutions by analyzing two key dimensions: normative perspectives and strategic approaches. From a normative standpoint, this study explores the legal and religious foundations governing corporate zakat obligations, as outlined in Law No. 23 of 2011 on Zakat Management and reinforced by the Indonesian Ulema Council (MUI) Fatwa No. 8 of 2011. From a strategic perspective, it highlights the role of the Zakat Compliance Label (Label Taat Zakat) and Zakat Payment Receipt (Bukti Setor Zakat) as tools to enhance transparency, accountability, and corporate donor trust toward the National Board of Zakat (BAZNAS). Using a qualitative descriptive approach through document analysis and in-depth interviews, data was processed using tabulation, proportion calculation, year-on-year growth, and classification based on the type of company (general and sharia) and type of funds (corporate zakat). In addition, a comparative analysis was conducted between years to identify patterns of fluctuations, retention, and the tendency of the company's contribution to the total collection. The data source comes from the internal reports of the Company's Zakat Division. This study contributes to Islamic philanthropy in companies by showing how normative and strategic instruments interact within state sanctioned zakat institutions. In terms of policy, these findings advocate cross sectoral collaboration between zakat authorities, regulatory bodies, and business associations to optimize corporate zakat governance.Keywords : Corporate Zakat, Normative Perspective, Strategic Approach, Islamic Philanthropy, BAZNAS